2004
DOI: 10.1124/mol.104.000893
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of Frequency Dependence and Ca2+ Potentiation of Verapamil Block in the Pore Region of Cav1.2

Abstract: Verapamil block of Ca v 1.2 is frequency-dependent and potentiated by Ca 2ϩ . We examined the molecular determinants of these characteristics using mutations that effect Ca 2ϩ interactions with Ca v 1.2. Mutant and wild-type Ca v 1.2 channels were transiently expressed in tsA 201 cells with ␤ 1b and ␣ 2 ␦ subunits. The four conserved glutamates that compose the Ca 2ϩ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
20
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 28 publications
(48 reference statements)
4
20
1
Order By: Relevance
“…We estimated a lower bound for verapamil affinity by measuring the inhibition of peak currents under conditions in which channels were fully available at the holding potential, fully activated at the current-eliciting potential, and the duration between consecutive pulses was long. Channels depolarized from Ϫ130 to Ϫ10 mV at a frequency of 0.2 Hz exhibited an IC 50 of 21.4 M, a value less than the affinities of 40.5 and 120 M reported for low-frequency stimulation of L-type channels in heterologous systems (Motoike et al, 1999;Dilmac et al, 2004) and similar to the values previously reported for T channels in native tissues (Kuga et al, 1990;Arnoult et al, 1998). The experimental data were fit well by a single-site binding curve, suggesting that drug binding was not a cooperative process (Fig.…”
Section: Resultssupporting
confidence: 53%
See 4 more Smart Citations
“…We estimated a lower bound for verapamil affinity by measuring the inhibition of peak currents under conditions in which channels were fully available at the holding potential, fully activated at the current-eliciting potential, and the duration between consecutive pulses was long. Channels depolarized from Ϫ130 to Ϫ10 mV at a frequency of 0.2 Hz exhibited an IC 50 of 21.4 M, a value less than the affinities of 40.5 and 120 M reported for low-frequency stimulation of L-type channels in heterologous systems (Motoike et al, 1999;Dilmac et al, 2004) and similar to the values previously reported for T channels in native tissues (Kuga et al, 1990;Arnoult et al, 1998). The experimental data were fit well by a single-site binding curve, suggesting that drug binding was not a cooperative process (Fig.…”
Section: Resultssupporting
confidence: 53%
“…1). Although verapamil has been reported to speed the decay of L-type currents (Hockerman et al, 1995(Hockerman et al, , 1997Johnson et al, 1996;Nawrath and Wegener, 1997;Motoike et al, 1999;Dilmac et al, 2004), it did not affect the T-channel current time course.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations